Penguatan Kecerdasan Linguistik Sebagai Penunjang Bisnis Dan Financial Sustainability Pada Usaha Mikro Di Desa Wisata Pulau Mubut - Sugeng Riadi; Yulinda Yulinda; Andi Erna Mulyana; Mia Syafrina; Desi Ratna Sari; Rizka Destiana; Slamet Soebagyo (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2022)
Mubut village is a built village that will be developed into a tourist village on Batam Island. This is necessary for the readiness of human resources on the island to contribute to the development of tourist villages. One of the human resources that need to be improved is the ability of micro-businesses and rural communities in their linguistic intelligence that is able to communicate with business English. With the linguistic intelligence possessed, it can contribute to its business activities and ultimately the level of financial sustainability is well maintained. The purpose of community service activities is to improve the competence of Mubut village community in improving linguistic intelligence (communication with English) in order to develop a built tourist village. The method that will be implemented is to conduct training offline, provide pocket books and simulation videos. The expected results are the existence of training materials, the availability of pocketbooks and video tutorials on how to easily communicate business English that can be accessed by micro-businesses and the public. This community service is one of the applications of Project-Based Learning for Business English subjects II, Managerial Accounting and Marketing also Business Finance for Business Administration Study Program.